"Free Gingival Grafting; Epiglu VS. Silk Thread Suturing: A Comparative Study " - M. Paknejad; Y. Soleymani Shayesteh; A. Esmaielieh (Tehran University of Medical Sciences, 2004)
Statement of the Problem: The routine procedure for immobilization of free gingival graft (FGG) is suturing. Due to the successful application of tissue adhesives their employment has also become the subject of interest. Purpose: The aim of present clinical trial was to compare using Epiglu (E.g) versus silk thread suturing in FGG. Materials and Methods: This study was a split mouth clinical trial. The study group comprised of 12 patients with symmetrical loss of attached gingiva whom were referred to Faculty of Dentistry, Tehran University of Medical science. In test group, the gingival graft were placed on cellophane and after applying one drop of Eg then placed in the proper position. In control group silk suturing was used. Results: The degree of pain had no significant differences in two groups (P>0.05). The rate of bleeding was insignificant at the first day (P=0.5), but in the second (P=0.0425) and the third day (P=0.0313) less bleeding was observed in the test group. 10 days after the surgery, grafts in the test group had better healing (P=0.0425), while 3 month later no significant differences observed (P>0.05). Although the mean tissue shrinkage were 41% and 38% for control and test group respectively, Wilcoxon test showed no significant differences 30 days after surgery (P>0.05). The tissue shrinkage also was not significant 3 months after surgery. In addition, no displacement, infection or hypersensitivity were noted in either of two groups. Conclusion: In FGG, Epiglu is more effective than suturing.